2013
DOI: 10.1007/s12032-013-0521-z
|View full text |Cite
|
Sign up to set email alerts
|

CYP2A6, CYP1A1, and CYP2D6 polymorphisms in lung cancer patients from Central South China

Abstract: Lung cancer is a common cause of cancer-related death. The link between risk of lung cancer susceptibility and genetic polymorphisms in metabolic enzymes is well documented. In this study, the relationships between lung cancer susceptibility and polymorphisms in the phase I metabolic enzyme genes CYP1A1, CYP2D6, and CYP2A6 were investigated. Genomic DNA was isolated from the peripheral blood of 201 healthy controls and 168 lung carcinoma patients from the Han ethnic group of Hunan Province in Central South Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Research carried out in the last decade demonstrated that several CYP enzymes are polymorphic due to single nucleotide polymorphisms, gene duplications and deletions. Consistent evidences for association between CYP polymorphisms and lung, head and neck, and other types of cancer were reported (Gattas et al, 2006;Huang et al, 2013;Hussein et al, 2014;Yang et al, 2015) However, report for association of CYP polymorphism and NPC is very rare to our knowledge. Glutathione S-transferases (GSTs) are phase II metabolic isozymes which catalyse converting glutathione (GSH) to xenobiotic substrates for the purpose of detoxification.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Research carried out in the last decade demonstrated that several CYP enzymes are polymorphic due to single nucleotide polymorphisms, gene duplications and deletions. Consistent evidences for association between CYP polymorphisms and lung, head and neck, and other types of cancer were reported (Gattas et al, 2006;Huang et al, 2013;Hussein et al, 2014;Yang et al, 2015) However, report for association of CYP polymorphism and NPC is very rare to our knowledge. Glutathione S-transferases (GSTs) are phase II metabolic isozymes which catalyse converting glutathione (GSH) to xenobiotic substrates for the purpose of detoxification.…”
Section: Introductionmentioning
confidence: 55%
“…Polymorphisms in glutathione-S-transferase genes (GSTM1 and GSTT1) and cytochrome p450 genes (CYP2E1, CYP1A1 and CYP2A6) are candidate cancer susceptibility genes (Gattas et al, 2006;Huang et al, 2013;Islam et al, 2013;Murthy et al, 2013;Russo et al, 2013;Jiang et al, 2014;Yang et al, 2015). Their association with NPC has been reported in some ethnic groups (Tiwawech et al, 2006;Murthy et al, 2013;Russo et al, 2013;Wei et al, 2013;Yang et al, 2015) [.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when the original studies included both smokers and non-smokers, the association between the CYP2A6 polymorphism genotype and risk of lung cancer may have been attenuated. This may explain why some of the studies did not find any significant association 19,20,29,42 .…”
Section: Discussionmentioning
confidence: 96%
“…癌症是一种严重危害人类健康的常见病、多发病 [1,2] ,在所有类型的癌症中,肺癌的死亡率在 5 年内高 达 80%~85% [3,4] 。癌症是细胞失控生长的复杂疾病, 而人类复杂疾病是由多个基因共同作用导致的 [5,6] 。 当 代,人类复杂疾病研究的一个重要挑战是寻找与疾病 相关的基因及基因之间的协同关系,并全面阐明其在 复杂疾病致病过程中的作用机理 [7,8] 和 Wang K.等人 [34] 的研究发现,新城鸡瘟病毒 NDV 具有潜在的溶瘤作用,它可以通过影响 MAPK 通路, 进而诱导肿瘤细胞凋亡。在模块 352 中还发现存在与 NDV 密切相关的 ISG15 和 MUC4 等基因。Lu G.等 [35] 发现,IRF-3 在抗病毒免疫反应过程中起到了重要作 用;而基因 ISG15 正是通过抑制 IRF-3 的降解,进而 增强个体的先天的抗病毒应答能力。Behr M.等人 [36] 使用 EMSA 实验方法,仅在病毒感染的 L929 细胞系 中发现与人干扰素刺激基因 ISG15 密切相关的蛋白质 复合物,这暗示着对该基因以及基因相关的生物学过 程进行研究或有可能揭示肺癌的内在机制。Nakaya T.…”
Section: 引言unclassified